Electrical Characteristics of Cobalt Phthalocyanine Complexes Adsorbed on Graphene - Cardenas-Jiron, G; Cortes-Arriagada, D (2011)
We investigate, at a density functional level, the electric characteristics of 18 complexes of cobalt phthalocyanine (CoPc) and cobalt tetraaminephthalocyanine (CoTAPc) adsorbed on graphene functionalized with CO2- or CO moieties. Three models of graphene molecules are used, pristine, defect, and vacancy, leading to 12 complexes with CO 2- functionalized graphene and 6 complexes with functionalized CO graphene. The molecular structures of the optimized complexes feature covalent adsorption Co-O lengths of ?1.9-2.1 Å and C-N lengths of ?1.4 Å in parallel, perpendicular, and coplanar structures of graphene with phthalocyanine. All these conformations have a direct effect on the electronic characteristics of the complexes. Binding energies calculated for the interaction between functionalized graphene and phthalocyanine show that structures with defects and vacancies have lower energies than pristine graphene. In particular, we found that complexes having a graphene-CO linked to phthalocyanine by an amide bond are of highest stability (by ?130 kcal/mol) and the formation of complexes with CO2- functionalized graphenes takes place preferably when involved with CoTAPc (by ?20 kcal/mol). Frontier molecular orbitals (HOMO and LUMO) suggest that several of these complexes behave as charge transfer compounds with phthalocyanine as an electron donor and graphene as an electron acceptor, thus these complexes could behave as sensors because of the absorption properties of phthalocyanine in the UV-vis region. The calculated current-voltage characteristics show that electron transfer is preferably favored in complexes with parallel structure and with pristine graphene CO2- functionalization (?7 ?A) when both conjugates, graphene and phthalocyanine, face each other. The latter implies the transfer of charge through a ?-? setting. However, the presence of defects and vacancies, for this face to face structure, shows lower electron transfer, having G-Def and G-Vac similar values of electron transfer. The conduction is very low for complexes with high stability (usually the coplanar structures) and with charge transfer features, i.e., those in which the HOMO and LUMO are in separated parts of the complex (usually the perpendicular and the coplanar structures). This study shows that cobalt phthalocyanine conducts electrical current toward graphene through a covalently attached CO2- to the graphene. © 2011 American Chemical Society.